2016
DOI: 10.1007/s10773-016-3067-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Universe with Particle Production

Abstract: The possibility of an emergent universe solution to Einstein's field equations allowing for an irreversible creation of matter at the expense of the gravitational field is shown. With the universe being chosen as spatially flat FRW spacetime together with equation of state proposed in [17], the solution exists when the ratio of the phenomenological matter creation rate to the number density times the Hubble parameter is a number β of the order of unity and independent of time. The thermodynamic behaviour is al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, such an equation of state gives rise to exotic matter. In [40], it was shown using the matter creation formulation [41], that one can get an emergent universe using the standard equation of state p = Ωρ. But in this study we find that the RG flow of the Newton's gravitational constant and cosmological constant with proper choice of cut-off functions, leads to an emergent universe solution using the standard equation of state p = Ωρ.…”
Section: Scale Factor For Different Cut-off Choicesmentioning
confidence: 99%
“…However, such an equation of state gives rise to exotic matter. In [40], it was shown using the matter creation formulation [41], that one can get an emergent universe using the standard equation of state p = Ωρ. But in this study we find that the RG flow of the Newton's gravitational constant and cosmological constant with proper choice of cut-off functions, leads to an emergent universe solution using the standard equation of state p = Ωρ.…”
Section: Scale Factor For Different Cut-off Choicesmentioning
confidence: 99%
“…The formalism augments the field equations of Einstein by introducing a conservation equation for particles. In a recent paper [15], it has been shown that one can have an emergent universe scenario in the context of this formalism which allows for an irreversible creation of matter at the cost of the field of gravitation.…”
Section: Introductionmentioning
confidence: 99%